Exploring Classroom Assessment Practices: Perspectives from Senior High School Teachers in Greater Accra, Ghana - Quainoo, Eric Atta; Bortey, Joana; Sundeme, Benjamin; Brew, Evans Austin (Journal of Interdisciplinary Studies in Education, 2023)
This study used a quantitative research design with a descriptive approach to investigate the assessment conceptions of teachers at senior high schools in Ghana’s Greater Accra Region. A sample of 280 senior high school teachers was selected using multi-stage sampling techniques, and data was collected using questionnaires adopted from Brown (2004). The data were analyzed using frequencies, percentages, mean, and standard deviation. Findings show that teachers conceive assessment as being for improvement and irrelevant. Recommendations are made to enhance senior high school teachers’ understanding of assessment as a tool for improvement and to encourage adherence to basic assessment practices.